PENINGKATAN MUTU KERUPUK PANGAN LOKAL PADA USAHA RUMAH TANGGA DI DESA LINGGA, KUBU RAYA - Dewi, Yohana Sutiknyawati Kusuma (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2019)
The second year of Ipteks bagi Desa Mitra (IbDM) programs have been done at Lingga village Kubu Raya Regency. The aims of this programs were preparing of human resources able to produce cracker products according to SNI and its packaged with labels so that its was increasing of her family income. The target audience in the second year was a member of the PKKs of Lingga Dalam and Remaja Masjid group. The method was used evaluation and socialization, assistance, evaluation and monitoring. The cracker quality assurance is enhanced through production system by semi-mechanical cracker slicers and solar dryers. The two devices to produce crackers that its have uniform thickness and safety of contaminants during drying. Quality assurance is also carried out by enhancing the administration of both the production and marketing of crackers. The entire IbDM programs has an impact on improving the quality of products, partner income and consumer confidence. Keywords: PPM, IbDM, Crackers, Lingga, quality